Hubungan Outdor Activity dengan Scene Setting dalam Skill Mengajar Pembelajaran IPA Mahasiswa PGSD Universitas Cokroaminoto Palopo - Andi Kilawati; Rosmalah Yanti (Universitas Cokroaminoto Palopo, 2019)
This study generally aims to determine the relationship of outdoor activity with Scene Settings in Elementary School Science Learning PGSD University Students Cokroaminoto Palopo. This research is a quantitative research. The research model used in this study is the correlational model. This research hypothesis was tested using two-way analysis of variance (ANAVA). The sample of this study was PGSD University Cokroaminoto Palopo University. The results of this study indicate that: (1) there is a positive relationship between outdoor activities and scene settings (2) there is a positive positive relationship between outdoor activities and scene settings in science learning of PGSD students at Cokroaminoto Palopo University.